2021
DOI: 10.18502/jmehm.v14i11.7666
|View full text |Cite
|
Sign up to set email alerts
|

Developing and validating an instrument to measure: the medical professionalism climate in clinical settings

Abstract: This study was conducted to develop and validate an instrument to measure the medical professionalism climate in clinical settings. The item pool was developed based on the Tehran University of Medical Sciences Guideline for Professional Conduct. The items were distributed between two questionnaires, one for health-care providers and the other for patients. To assess the construct validity of the questionnaires, 350 health-care providers and 88 patients were enrolled in the study. The reliability of the questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Ashgari and colleagues presented a different questionnaire to residents, staff physicians, nurses and patients [24]. They found that residents scored the professionalism environment lower than nurses and faculty members, perhaps because of their increased sensitivity to its aws.…”
Section: Limitationsmentioning
confidence: 99%
“…Ashgari and colleagues presented a different questionnaire to residents, staff physicians, nurses and patients [24]. They found that residents scored the professionalism environment lower than nurses and faculty members, perhaps because of their increased sensitivity to its aws.…”
Section: Limitationsmentioning
confidence: 99%
“…In Moudatsou et al's study, some of the factors that negatively influence the development of empathy are the lack of adequate time, the focus on therapy within the existing academic culture, the high number of patients that professionals have to manage, and the lack of education in empathy (25). In an unprofessional environment, professional practice can hardly take place (32). Providing the context to have professional behavior (including empathy) is a matter that should be taken into consideration by the authorities.…”
Section: Compliance With Professionalismmentioning
confidence: 99%